What's wrong with democracy? : from Athenian practice to American worship - Samons, Loren J., II. (Berkeley : University of California Press, 2004)
In this daring reassessment of classical Athenian democracy & its significance for the United States today, Samons firstly shows why the Athenian model was distrusted by America's founding father, before considering how the concept of democracy has now become an object of popular veneration.
Introduction -- Athenian society and government -- Democracy and demagogues : election, voting, and qualifications for citizenship -- Public finance : democracy and the people's purse -- Foreign policy I : democracy imperial -- Foreign policy II : the Peloponnesian War -- National defense : democracy defeated -- Democracy and religion -- Conclusion : Socrates, Pericles, and the citizen.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Democracy -- History; Direct democracy -- Greece -- Athens; Republicanism -- United States -- History; Representative government and representation -- United States; Political culture -- United States -- History; United States -- Civilization -- Greek influences; Démocratie directe -- Grèce -- Athènes.; Républicanisme -- États-Unis -- Histoire; Gouvernement représentatif -- États-Unis.; POLITICAL SCIENCE -- Political Ideologies -- Democracy; POLITICAL SCIENCE -- History & Theory; Civilization -- Greek influences; Democracy; Direct democracy; Political culture; Representative government and representation; Republicanism; Greece -- Athens; United States; american government; ancient greece; athenian democracy; athenian government; athenian society; choice; classical athenian democracy; democracy; democratic governments; dissent; diversity; elections; foreign policy; freedom; government and governing; government and religion; government; historical; history; national defense; peloponnesian war; political systems; political theory; politics; popular vote; public finance; qualifications for citizenship; religion; united states of america; voting; History